Sigma-1 Receptor is a Pharmacological Target to Promote Neuroprotection in the SOD1G93A ALS Mice - Gaja-Capdevila, Núria; Hernández, Neus; Navarro, Xavier; Herrando-Grabulosa, Mireia (Frontiers in Pharmacology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder characterized by the death of motoneurons (MNs) with a poor prognosis. There is no available cure, thus, novel therapeutic targets are urgently needed. Sigma-1 receptor (Sig-1R) has been reported as a target to treat experimental models of degenerative diseases and, importantly, mutations in the Sig-1R gene cause several types of motoneuron disease (MND). In this study we compared the potential therapeutic effect of three Sig-1R ligands, the agonists PRE-084 and SA4503 and the antagonist BD1063, in the SOD1G93A mouse model of ALS. Pharmacological administration was from 8 to 16 weeks of age, and the neuromuscular function and disease progression were evaluated using nerve conduction and rotarod tests. At the end of follow up (16 weeks), samples were harvested for histological and molecular analyses. The results showed that PRE-084, as well as BD1063 treatment was able to preserve neuromuscular function of the hindlimbs and increase the number of surviving MNs in the treated female SOD1G93A mice. SA4503 tended to improve motor function and preserve neuromuscular junctions (NMJ), but did not improve MN survival. Western blot analyses revealed that the autophagic flux and the endoplasmic reticulum stress, two pathways implicated in the physiopathology of ALS, were not modified with Sig-1R treatments in SOD1G93A mice. In conclusion, Sig-1R ligands are promising tools for ALS treatment, although more research is needed to ascertain their mechanisms of action.